MESIN PENCETAK LAKSA SISTIM VERTIKAL - Sisiylennia Sisylennia feby octory; Mahendra Dwi Cahyo S; Iqbal (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
Laksa is a typical Indonesian food that has a shape like noodle. Laksa is often known as “lakso” for the southern part of Sumatra, especially Palembang and Bangka Belitung. Based on the survey results, the printing process is still manual by hand so it requires a lot of time and energy. The purpose of this final project is to design and manufacture a laksa printing machine with a vertical system. With a capacity of 1,5 kg/5 minutes. The vertical system laksa printing machine design method uses the VDI 2222 design methodology which has 4 stages, namely planning, conceptualizin, designing and finishing. The results of the design and manufacture of this machine are able to process laksa printing with a dough capacity of 1,5kg in 5 minutes with a laksa diameter of 3 mm which is driven by a 1 phase motor. Within 1 hour able to print 18 kg.